Preliminary Study on Consumer Attitude towards FinTech Products and Services in Malaysia - Tat Huei, Cham; Suet Cheng, Low; Chee Seong, Lim; Aye Khin, Aye; Ling Leh Bin, Raymond (International Journal of Engineering and Technology, 2018)
â€œFinTechâ€ or a compound term of Financial Technology refers as a newly emerged industry that utilizes IT-centered technologies which aims to boost the efficiency of the financial ecosystem. Since its inception, FinTech has successfully established its presence in the global financial industry due to the benefits and advantages of the system. However, the research studies that highlight the importance of FinTech are scarce. Specifically, the study pertaining to the consumersâ€™ attitude towards FinTech products and services in the context of Malaysia remains unexplored by most of the studies. This preliminary study proposed the extension of Technology Acceptance Model (TAM) to identify the potential factors that influence consumersâ€™ intention to adopt FinTech products and services in Malaysia. This study reviewed the factors, namely the usefulness, ease of use, competitive advantage, perceived risk, and perceived cost that can potentially influence the attitude of customers towards the product and services of FinTech. This study also proposes the potential mediating effect of attitude towards using FinTech products and the intention to adopt FinTech. This study attempts to create new knowledge geared towards the behavior to utilize FinTech products in Malaysia.